Incident-centered information security: Managing a strategic balance between prevention and response - Baskerville, Richard; Spagnoletti, P.; Kim, J. (Elsevier, 2014)
Information security strategies employ principles and practices grounded in both the prevention andresponse paradigms. The prevention paradigm aims at managing predicted threats. Although theprevention paradigm may dominate in contemporary commercial organizations, the response paradigm (aimed at managing unpredicted threats) retains an important role in protecting information security in today’s dynamic threat environment. This study provides an overarching security framework that focuses on managing the proper balance between prevention and response paradigms. We conduct a comparative case study with three European organizations. This study analyzes and empirically confirms how and why organizations balance between their prevention and response strategies.